Bibliometric analysis: The reputation of Indonesian law enforcement officials on social media - Indira Restu Valentina; Iip Permana (Priviet Social Sciences Journal, 2025)
Law enforcement plays a crucial role in maintaining public safety and welfare, making the reputation of law enforcement agencies a key concern, particularly in the digital space. This study maps the research landscape of the reputation of law enforcement organizations on social media through a bibliometric approach. Data was collected from Google Scholar using Publish or Perish (keywords: "organizational reputation," "law enforcement," "social media"; period 2020–2025), cleaned in Mendeley, manually selected for relevance (PRISMA), descriptively analyzed using Excel, and mapped with VOSviewer (network, overlay, density). A total of 100 publications were collected, with the trend showing a sharp increase in the last three years, contributing 83 publications out of the total, indicating a shift from the periphery to the mainstream. Using VOSViewer visualization, four clusters were identified in this study. Overlay shows a shift from a protective focus to digital communication management and public legitimacy; density highlights density in "media,” "law,” "Indonesia" and "data" and gaps in "credibility,” "Instagram" and "victim.” This trend shows a relationship between the reputation of law enforcement agencies and good, data-driven, and transparent digital communication strategies. However, there is a need for further research on the credibility, effectiveness, regulation, and performance of law enforcement agencies.